The Importance of Understanding Student Character to Support Successful Learning in Junior High School - Sulkifli Sulkifli (Jurnal Konsepsi, 2021)
This research is a type of descriptive qualitative and quantitative research, raising the problem of teachers' understanding of student characteristics in supporting student learning success in learning. Therefore, this study was analyzed using qualitative techniques and processed by describing the data in the form of tabulation of the data from the percentage of the questionnaire to students and teachers as research samples or respondents. The population of this study was all students and teachers of SMPN 2 Bulukumba, Bulukumba Regency, so it was determined as a sample of 20 students and 12 class teachers. The results showed that at SMPN 2 Bulukumba, through the efforts or methods made by the teacher in understanding the characteristics of students, the average teacher used several methods such as the observation method by visiting the house and the method of using the test, and the positive effect felt by the teacher is that it increases student learning outcomes and makes it easier for teachers to carry out the learning process. Therefore, it is very important for all teachers, both as homeroom teachers and field teachers, to understand the characteristics of each student.